Kajian Implementasi Jaminan Kesehatan Nasional Lintas Provinsi (Sulawesi Selatan, Sulawesi Tenggara, Sulawesi Barat) Tahun 2014 - Alimin Maidin; Sukri Palutturi (Center for Health Policy and Management, 2016)
ABSTRACTBackground: Changes in health financing towards Universal Health Coverage (UHC) is to provide benefits, but on the other hand have a negative impact and the risks. Implementation of the National Health Insurance should be monitored in order to achieve the level of satisfaction of 80% against BPJS of health facilities.Aims: Monitoring and evaluating the implementation and the barriers to formulate policy recommendations on the improvement of the National Health Insurance program (JKN) in the province of South Sulawesi, Southeast Sulawesi and West Sulawesi in 2014; explained various aspects of the progress and challenges on political and institutional transformation program, advocacy and socialization, participation, service infrastructure at health facilities, referral system, Human Resources and Capacity Building; explained various aspects of the progress and challenges of financing, the risk of fraud, and the impact on utilization, satisfaction of participants and providers.Methods: This study used a qualitative approach. This research was conducted in the Province of South Sulawesi (Makassar City and Jeneponto), South East Sulawesi (Kendari and Konawe) and W est Sulawesi (Mamuju and Majene regency). The selection of respondents was done by using purposive sampling technique. Informants were from different elements: Hospitals, BPJS, Health Center, Health Department, Bappeda, Family Doctor and patient. Data were collected by using indepth interviews and review documents. Analysis of the data was using triangulation techniques either method and source triangulations.Results: There are still many problems, especially at the initial stage of implementation JKN. Problems related to aspects of political and institutional transformation program, advocacy and socialization of program JKN, membership, service infrastructure at health facilities, referral system and Human Resources and capacity building, aspects of financing, the risk of fraud in the implementation of JKN, and the impact JKN against utilization, satisfaction of participants and providers. Conclusion:Guarantee to quality of service by providers and patients will increase if policies and institutional transformation program, advocacy and socialization of program JKN, JKN membership, service infrastructure at health facilities, referral system and Human Resources and capacity building are strengthened and improved. It also covers aspects offinancing, the risk of fraud in the implementation of JKN and JKN impact on utilization, satisfaction of participants and providers. Keywords: JKN, South Sulawesi, Southeast Sulawesi, West Sulawesi ABSTRAKLatar belakang: Perubahan pembiayaan kesehatan menuju Universal Health Coverage ( UHC) merupakan hal yang menjanjikan namun pada sisi lain mempunyai dampak dan risiko. Pelaksanaan JKN perlu dipantau agar dapat tercapai tingkat kepuasan 80% terhadap BPJS dari fasilitas kesehatan.Tujuan: Memonitoring dan mengevaluasi pelaksanaan dan hambatan untuk merumuskan rekomendasi kebijakan perbaikan program Jaminan Kesehatan Nasional (JKN) di Provinsi Sulawesi Selatan, Sulawesi Tenggara, dan Sulawesi Barat pada tahun 2014; memaparkan berbagai kemajuan dan tantangan pada aspek kebijakan dan kelembagaan, transformasi program, advokasi dan sosialisasi, kepesertaan, infrastruktur pelayanan pada fasilitas kesehatan, sistem rujukan, SDM dan Capacity Building; memaparkan berbagai kemajuan dan tantangan dari aspek pembiayaan, risiko terjadinya Fraud, dan dampak terhadap utilisasi, kepuasan peserta dan provider.Metode: Penelitian ini menggunakan pendekatan kualitatif. Penelitian ini dilakukan di Provinsi Sulawesi Selatan (Kota Makassar dan Kabupaten Jeneponto), Provinsi Sulawesi Tenggara (Kota Kendari dan Kabupaten Konawe) dan Provinsi Sulawesi Barat (Kabupaten Mamuju dan Kabupaten Majene). Pemilihan responden dilakukan dengan menggunakan teknik Purposive Sampling. Informan berasal dari berbagai unsur: Rumah Sakit, BPJS, Puskesmas, Dinas Kesehatan, Bappeda, Dokter Keluarga, dan pasien. Pengumpulan data dilakukan dengan menggunakan indepth interview dan telaah dokumen. Analisis data menggunakan teknik triangulasi baik triangulasi metode maupun triangulasi sumber.Hasil: Masih banyak ditemukan berbagai masalah dalam pelaksanaan JKN terutama pada tahap awal pelaksanaannya. Masalah yang berkaitan dengan aspek kebijakan dan kelembagaan, transformasi program, advokasi dan sosialisasi program JKN, kepesertaan, infrastruktur pelayanan pada fasilitas kesehatan, system rujukan dan Sumber Daya Manusia dan Capacity Building, aspek pembiayaan, risiko terjadinyaFraud pada pelaksanaan JKN, dan dampak JKN terhadap utilisasi, kepuasan peserta dan provider.Kesimpulan: Jaminan kualitas pelayanan oleh provider dan pasien akan meningkat jika asapek aspek kebijakan dan kelembagaan, transformasi program, advokasi dan sosialisasi program JKN, kepesertaan JKN, infrastruktur pelayanan pada fasilitas kesehatan, system rujukan dan Sumber Daya Manusia dan Capacity Building diperkuat dan ditingkatkan. Selain itu juga mencakup aspek pembiayaan, risiko terjadinya Fraud pada pelaksanaan JKN, dan dampak JKN terhadap utilisasi, kepuasan peserta dan provider. Kata Kunci: JKN, Sulawesi Selatan, Sulawesi Tenggara, Sulawesi Barat